2012
DOI: 10.1039/c1cc14643b
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule magnetism in cyclopentadienyl-dysprosium chlorides

Abstract: [Cp(2)Dy(thf)(μ-Cl)](2) (2) was synthesized from [Cp(2)Dy(μ-Cl)](n), which crystalizes as two polymorphs, with n = 2 (1a) or ∞ (1b). All three compounds show slow relaxation of magnetization, and in 2 the quantum tunnelling was found to be exchange-biased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
67
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(76 citation statements)
references
References 28 publications
9
67
0
Order By: Relevance
“…Increases in the magnetic-anisotropy barrier have recently been achieved by the use of lanthanide ions, which possess large single-ion magnetic anisotropies. This has resulted in the development of several mono-and polynuclear compounds displaying energy barriers to magnetic reversal of up to 938 K, [4] an order of magnitude larger than the barrier of 60 K displayed by the prototype SMM, the iconic [Mn 12 (OAc)] complex. [5] Although large thermal energy barriers can be achieved through the use of lanthanide ions, additional processes, such as rapid quantum tunneling of the magnetization (QTM), which shortcuts the relaxation barrier and is fast in many lanthanide containing complexes at zero magnetic field, hamper the appearance of hysteresis with large coercive fields.…”
mentioning
confidence: 99%
“…Increases in the magnetic-anisotropy barrier have recently been achieved by the use of lanthanide ions, which possess large single-ion magnetic anisotropies. This has resulted in the development of several mono-and polynuclear compounds displaying energy barriers to magnetic reversal of up to 938 K, [4] an order of magnitude larger than the barrier of 60 K displayed by the prototype SMM, the iconic [Mn 12 (OAc)] complex. [5] Although large thermal energy barriers can be achieved through the use of lanthanide ions, additional processes, such as rapid quantum tunneling of the magnetization (QTM), which shortcuts the relaxation barrier and is fast in many lanthanide containing complexes at zero magnetic field, hamper the appearance of hysteresis with large coercive fields.…”
mentioning
confidence: 99%
“…The discussion starts with the smallest possible monoatomic bridging ligands like OH − , O 2− , S 2− , F − , Cl − , etc. 5), reported by Winpenny et al 13 The dimer complex contained eight-coordinate Dy III ions coordinated by the strong crystal field ligand cyclopentadiene (Cp = η 5 -C 5 H 5 ). So, using such ligands, large numbers of magnetic cages have been reported and some of them are very interesting in terms of structure and magnetic properties.…”
Section: A Choice Of Ligandsmentioning
confidence: 91%
“…(H 2 O)9 ](ClO 4 ) 29 ·(H 2 O) 80 ·(C 2 H 5 OH)4 (13),29 which were obtained through the self-assembly of metal ions and myoinositol ligand. Structural investigation revealed that the compounds are made up of two [Dy 9 M(OH) 4 (CH 3 COO)6 -(C 6 H 10 O 6 ) 3 (C 6 H 9 O 6 ) 3 (H 2 O) 15 ] 4+ units, three [Dy 2 (H 2 O) 7 ] 6+ units and three non-coordinating ClO 4− anions acting as templates.Each of the M II ions is hexa-coordinated whereas the Dy III ions are in hepta-coordinate, octa-coordinate and nona-coordinated environments.…”
mentioning
confidence: 99%
“…These ions have a large D parameter because of their diffuse valance orbitals and consequent significant unquenched orbital angular momentum, which renders strong spin–orbital coupling (SOC). Recent reports describing systems such as [Dy 4 K 2 O(O t Bu) 12 ], [Dy 5 O(O i Pr) 13 ], [Cp 2 Dy(thf)(µ‐Cl)] (Cp = cyclopentadiene), and [(Cp*2Ln) 2 (µ‐bpym)] + (Cp* = pentamethylcyclopentadienyl; bpym = 2,2′‐bipyrimidine; Ln = Gd 3+ , Tb 3+ ) have motivated synthetic chemists to prepare new families of lanthanide complexes with the hope of achieving a new family of SMMs.…”
Section: Introductionmentioning
confidence: 99%